Fertility life tables of Raoiella indica (Trombidiformes: Tenuipalpidae) at different temperature and humidity levels. (2019)
A study of fertility life tables of Raoiella indica was carried out on coconut (Cocos nucifera) leaflets at controlled temperature and relative humidity (RH) in Texcoco, Mexico, with the objective of estimating the parameters of population increase of this mite. Cohorts of 12-hour-old Raoiella indica eggs were incubated at 22.5, 25, 27.5 or 30 °C and 40-50 % RH, as well as 27.5 °C with 30-40, 60-70 or 80-90 % RH. They were observed daily until the last mite died. Females that attained adulthood were provided with two males to promote mating and their oviposition was recorded daily. Each one-day-old male was put in contact with a female quiescent deutonymph daily to determine how many times a male could copulate after the deutonymph became an adult. With all temperatures and RH’s, mortality was evenly distributed throughout the observations. Developmental rate, reproduction, and, consequently, parameters of population increase were significantly associated with temperature. The highest rate of population increase took place at 27.5 °C and 40-40 RH. By itself, RH did not significantly affect those variables, although its extreme values showed slight negative effects. Approximately four females per male were observed. Males copulated with 4.56 females on average; this suggests that between 20 and 30 % of the males are enough to fertilize all females present.